Evaluating Reading and Mathematics Instruction for Students With Learning Disabilities: A Synthesis of Observation Research - McKenna, John William; Shin, Mikyung; Ciullo, Stephen (Learning disability quarterly, 2015)
Systematically observing instruction for students with learning disabilities (LD) provides information regarding the quality of school-based interventions, allocation of instructional time, and other implementation variables associated with student outcomes. In this synthesis, observation studies of reading and mathematics instruction from 2000 to 2013 were identified through a systematic literature search. The purpose was to understand findings from observations of typical practice for students with LD during an era of increased exposure to evidence-based practices, educational policy reforms, and reports on reading and mathematics designed to influence instruction, and amid a period of increased academic expectations. Eleven studies focusing on academic instruction for students with LD were identified and reviewed. Cognitive strategy instruction, differentiated instruction, and opportunities for independent application (i.e., text reading, problem solving) were reported infrequently across the published observational research. However, findings provide some evidence of improved teacher use of effective instructional practices in several areas compared with earlier observation study syntheses. Implications for practice and areas for future research are discussed.